KETIMPANGAN DALAM SISTEM BAGI HASIL PERTANIAN: TINJAUAN FIQIH TERHADAP MUSĀQAH DAN MUZĀRA‘AH - Ikhlash Hidayatullah; Jefri Ariansyah Putra; Mhd. Khairi Siddqi; Gusti M. Abdurrahman Yahya Ayyasy; Fatmah Taufik Hidayat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Profit-sharing systems in the agricultural sector represent a long-standing form of economic cooperation, including within Islamic tradition through the contracts of musāqah and muzāra‘ah. In Islamic jurisprudence (fiqh al-mu‘āmalāt), these contracts are founded upon principles of justice (al-‘adl), proportionality between profit and risk (al-ghunm bi al-ghurm), and public benefit (al-maṣlaḥah). However, in contemporary practice, agricultural profit-sharing systems often experience distortions that lead to inequality between landowners and cultivators. The findings reveal that inequality in agricultural profit-sharing systems arises from deviations from the fundamental principles of musāqah and muzāra‘ah, including contractual ambiguity (gharar), unequal risk distribution, and exploitative practices (ẓulm). In many cases, cultivators bear a disproportionate share of production costs, while profit distribution fails to reflect the principles of fairness emphasized in Islamic jurisprudence. This condition contradicts the Qur’anic prohibition against unjust appropriation of wealth (Qur’an 4:29). Therefore, it is necessary to reconstruct agricultural profit-sharing practices by re-aligning them with the core principles of fiqh al-mu‘āmalāt, emphasizing justice, transparency, and balanced risk-sharing. The maqāṣid al-sharī‘ah approach is essential in formulating solutions that are not only legally valid but also socially equitable and sustainable in the contemporary era.